Equal pay petition, 1954 (1954)
1954 1945-1960 "Equal pay petition, 1954" [EP0050b], 1954 In 1954, a massive petition in support of equal pay was organised by the Equal Pay Coordinating Committee and presented to Members of Parliament at a demonstration on March 9. These photographs are in the February 1954 issue of Red Tape, the journal of the Civil Service Clerical Association.